(untitled) (Research, Society and Development, 2025)
This scientific article begins with the premise that the rising levels of violence in communities demand new policing strategies. In this context, the following question emerged: how can itinerant policing function as an efficient tool for reducing violence and crime in these communities by ensuring a visible police presence, saturating strategic areas, and enhancing regional security? The hypothesis guiding this study is that police presence inhibits criminal activity, transforming socially vulnerable communities into environments with lower levels of violence and crime. The objective of this work is to discuss how policing can be improved to enhance service quality in socially at-risk communities. The study is grounded in modern policing models established in the public security literature. The methodology adopted is bibliographic research. Among the main findings, social inequality stands out as a key factor contributing to the rise in crime and violence in high-risk communities, while itinerant policing proves to be an effective means of crime prevention, as the proposed model seeks to focus police efforts more intelligently on areas that require greater state attention.